Analysis of millisecond collision of composite high pressure hydrogen storage cylinder. (8th April 2023) - Zhang, Zhaomao; Yu, Feng; Qu, Dawei
Abstract: For vehicle-mounted high-pressure hydrogen storage cylinders, impact resistance is an important indicator. This work aims at building a model of 70 MPa composite fully wound Ⅳ cylinder around T800 carbon fiber material, investigating the law of transient changes in the body of the bottle under different velocity impacts and the source of risk of bursting. Through millisecond impact analysis, the energy transfer path and transformation trend inside the cylinder are obtained. Meanwhile, it was found that there was a clear pattern of positive correlation between the tensile and compressive stresses generated by the difference between the internal pressure of the bottle and the impact pressure. The final results show that after the impact, the failure occurred firstly at the inner wall of the fiber corresponding to the impact point, and the fiber damage spreads in all directions. The thickness of the failure pavement increases from the inside to the outside. Highlights: Exploration of the pressure change law when the hydrogen storage cylinder is subjected to high-speed impact. Demonstrate the trend of energy transfer during gas cylinder impact using millisecond impact analysis. Effect of hydrogen pressure inside the cylinder on impact. The impact is more damaging to the fibers on the inner wall of the cylinder, and the fiber layer fails from the inside out.